A systematic review and meta‐analysis of the effect of Vitamin D‐fortified food on glycemic indices. (29th April 2020) - Emadzadeh, Maryam; Sahebi, Reza; Khedmatgozar, Hamed; Sadeghi, Ramin; Farjami, Mahsa; Sharifan, Payam; Ravanshad, Yalda; Ferns, Gordon A.; Ghayour‐Mobarhan, Majid
Abstract: Some reports indicated that Vitamin D may improve glycaemia indices in diabetic patients. The aim of this systematic and meta‐analysis was to evaluate effects of Vitamin D fortification on indices of glycemic control. Six databases (PubMed/Medline, ISI Web of Knowledge, Cochrane Library, Science Direct, Scopus, and Google Scholar) were searched, for randomized controlled trials that were published up to September 2018 and that compared the effect of Vitamin D‐fortified food versus regular diet in relation to glycemic control. Of the 4, 379 studies originally found, 11 articles remained to be assessed for meta‐analysis. Vitamin D fortification was associated with a significant improvement in fasting serum glucose (mean difference [MD]: −2.772; 95% confidence interval [CI]: −5.435 to −0.109) and fasting serum insulin (MD: −2.937; 95% CI: −4.695 to −1.178) in patients with Type 2 diabetes mellitus. A diet with food enriched with Vitamin D was associated with a significant improvement in homeostatic model assessment of insulin resistance (MD: −1.608; 95% CI: −3.138 to −0.079) but was not associated with a significant reduction in hemoglobin A1C (MD: 0.034; 95% CI: −0.655 to 0.069). This meta‐analysis indicates that Vitamin D fortification improves indices of glycemic control. Hence, food fortified with Vitamin D may be of potential therapeutic value in diabetic patients, as an adjuvant therapy.